Elevation of IgE in patients with psoriasis: Is it a paradoxical phenomenon? - Shi, Leyao; Liu, Chen; Xiong, Huabao; Shi, Dongmei (Frontiers in Medicine, 2022)
Immunoglobulin E (IgE) elevation is a hallmark of allergic conditions such as atopic dermatitis (AD). The pathogenesis of AD is typically associated with high levels of IL-4 and IL-13 produced by activated T helper 2 (Th2) cells. Psoriasis, on the other hand, is an inflammatory skin disease mainly driven by Th17 cells and their related cytokines. Although the immunopathologic reactions and clinical manifestations are often easily distinguished in the two skin conditions, patients with psoriasis may sometimes exhibit AD-like manifestations, such as elevated IgE and persistent pruritic lesions. Given the fact that the effective T cells have great plasticity to re-differentiate in response to innate and environmental factors, this unusual skin condition could be a consequence of a cross-reaction between distinct arms of T-cell and humoral immunity. Here we review the literature concerning the roles of IgE in the development of AD and psoriasis, showing that elevated IgE seems to be an important indicator for this non-typical psoriasis.